Crop residue management to reduce GHG emissions and weed infestation in Central India through mechanized farm operations. Issue 6 (19th November 2020) - Chethan, C. R.; Singh, P. K.; Dubey, R. P.; Chander, Subhash; Gosh, Dibakar; Choudhary, V. K.; Fagodiya, Ram K.
ABSTRACT: Crop residue burning is a major issue in farmers' fields of Indo-Gangetic Plain and Central India. It emits air pollutants and GHGs into the atmosphere, adversely affects soil, crop yields, human health and the environment. Weed infestation is also a major problem and affects overall crop yield. Therefore, a 2-year farm experiment was conducted at farmers' fields with three treatments – current farmers' practice (FP), conservation agriculture with improved weed management (CAW) and conservation agriculture without any weed management (CA) – from kharif (monsoon) 2017 to summer 2019 to manage crop residue and weeds. A happy seeder and tractor-operated boom sprayer were also introduced in CA and CAW. Total 51 t of crop residue was generated from 2 ha of rice-wheat-greengram cultivation area. In FP this crop residue was burned, but it was utilized as mulch in CA and CAW, thus, emission of 34, 400 kg CO2 e was avoided and energy potential of 100.1 × 10 4  MJ was created. The CAW produced percent higher crop yield of 21, 22.5 and 44.4%in first year and 20.6, 20 and 30% in second year of crop cycle respectively in rice (4.6 & 4.1 t ha −1 ), wheat (4.9 & 4.1 t ha −1 ) and greengram (1.3 & 1.3 t ha −1 ).